Use of glucose for pain management in premature neonates: a systematic review and meta-analysis protocol - Ayane Cristine Alves Sarmento; Ana Paula Ferreira Costa; Ana Katherine Gonçalves; Kleyton Santos Medeiros; Débora Joyce Duarte Oliveira; Francisca Jennifer Duarte Oliveira; Nilba Lima Souza; Maria de Lourdes Costa Silva (BMJ Open)
Introduction Therapeutic management of neonatal pain is essential to reduce changes in initial and subsequent development. Although glucose has been shown to be effective in relieving pain, concentrations and dosages remain to be standardised. The objective of this systematic review and meta-analysis is to identify the efficacy of glucose as an analgesic in preterm infants.Methods and analysis The Web of Science, Science Direct, Scopus, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, PubMed, Medline, Latin American and Caribbean Health Sciences Literature and Embase databases will be researched for randomised studies published until December 2021. This systematic review and meta-analysis will include studies investigating the use of glucose for pain control in premature neonates. The primary outcome will be pain relief. Three independent reviewers will select the studies and extract the data from original publications. The risk of bias was assessed using the Cochrane risk of bias tool. Data synthesis will be performed using the Review Manager software (RevMan V.5.2.3). We will evaluate heterogeneity based on I2 statistics. In addition, quantitative synthesis will be performed if the included studies are sufficiently homogeneous.Ethics and dissemination Ethical approval for the research will not be required for this systematic review. The results of this study will be published in an international journal.Trial registration number This protocol was submitted to the International Prospective Register of Systematic Reviews (PROSPERO, number CRD42021236217).